STUDI KASUS PEMERIKSAAN THORAX PADA PASIEN TENGGELAM YANG MENGALAMI DEKOMPRESI - Siti Nur Hidayati; Cindy Oktavia Ningsi (JRI (Jurnal Radiografer Indonesia), 2022)
Background: Decompression is a disease caused by the release of air bubbles into the blood or body tissues during a very rapid decrease in surrounding pressure (decompression). Several cases of thorax examination in drowning patients who underwent decompression were carried out in different positions, namely the patient was supine or semi-erect. Methods: The research method used is qualitative with a descriptive approach, which carried out by means literature review, observation, interviews, and documentations. The research time is 6 months with a total sample of 10 samples. Results: Image analysis, comparison of thorax techniques in the field, and the results of the study were concluded by conducting interviews with 1 radiologist and 2 radiographers.. Conclusions: Examination of the thorax in a drowning patient who is decompressed can be performed with the patient in a supine or semi-erect position. The selection of patient position for thorax examination in drowning patients undergoing decompression is determined by looking at the general health condition of the patient. The position of the semi-erect patient is better so that it can produce a chest radiograph that is quite informative in showing lungs.